1995
DOI: 10.3109/02713689509033523
|View full text |Cite
|
Sign up to set email alerts
|

Cat model for intraocular pressure reduction after transscleral Nd:YAG cyclophotocoagulation

Abstract: Transscleral neodymium:yttrium-aluminum-garnet (Nd:YAG) laser cyclophotocoagulation (TSNYC) is used to lower intraocular pressure (IOP) in glaucoma patients refractory to conventional medical and surgical therapy. Our study investigates the ability of TSNYC to lower IOP in normal cats. One eye of 13 cats was treated with non-contact TSNYC. Mean pretreatment IOP was 25 mm Hg (vs. 25.3 mm Hg in contralateral control eyes). Eyes received 80 laser applications over 360 degrees delivered at least 3 mm posterior to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Lower amounts of energy (< 100 J) have been associated with only transient reduction of IOP. 5,48 Because of variations among subjects, amounts of power, exposure times, and degree of scleral and uveal pigmentation, it is difficult to define an optimal treatment protocol. 5,48,49 In the study reported here, as expected, there was a significant decrease in IOP in treated eyes at most time points after laser treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lower amounts of energy (< 100 J) have been associated with only transient reduction of IOP. 5,48 Because of variations among subjects, amounts of power, exposure times, and degree of scleral and uveal pigmentation, it is difficult to define an optimal treatment protocol. 5,48,49 In the study reported here, as expected, there was a significant decrease in IOP in treated eyes at most time points after laser treatment.…”
Section: Discussionmentioning
confidence: 99%
“…5,48 Because of variations among subjects, amounts of power, exposure times, and degree of scleral and uveal pigmentation, it is difficult to define an optimal treatment protocol. 5,48,49 In the study reported here, as expected, there was a significant decrease in IOP in treated eyes at most time points after laser treatment. The significant decrease in corneal sensitivity seen on all days after laser treatment documented that lower total energy delivery (eg, 100 J) is able to compromise corneal sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, there appears to be marked inter‐individual variation in the location of the ciliary processes relative to the limbus in glaucomatous cats and bupthalmia may further enhance this variation. In one experimental study, cyclophotocoagulation with Nd:YAG laser led to a mean reduction in IOP of about 30% in normal cats 86 . However, the chronic nature of IOP elevation in most glaucomatous cats and variable degree of associated globe enlargement make it difficult to determine the most appropriate site for trans‐scleral laser or cryosurgical application based solely on knowledge of the anatomy of normal cats.…”
Section: Topical Corticosteroids: Indications and Contraindicationsmentioning
confidence: 99%
“…In one experimental study, cyclophotocoagulation with Nd:YAG laser led to a mean reduction in IOP of about 30% in normal cats. 86 However, the chronic nature of IOP elevation in most glaucomatous cats and variable degree of associated globe enlargement make it difficult to determine the most appropriate site for trans-scleral laser or cryosurgical application based solely on knowledge of the anatomy of normal cats. Pre-operative ultrasound biometry, as an aid to determining the location of the ciliary body in individual glaucomatous cats, could feasibly increase the success rate of surgical, cyclodestructive procedures.…”
Section: Cyclodestructive Proceduresmentioning
confidence: 99%
“…The goal of this procedure is the coagulation of the ciliary epithelium and stroma of the pars plicata where aqueous humor is produced, without causing marked architectural disruption and loss of anatomic integrity 19 . TSCP has been reported in dogs, 20–27 cats, 28,29 horses, 7,13,30 rabbits 31,32 and humans 33–38 . It is theorized that the reduction in IOP associated with TSCP is the result of destruction of the ciliary epithelium thereby reducing aqueous production 39,40 .…”
Section: Introductionmentioning
confidence: 99%